Il10 deficiency re-balances innate immunity to mitigate Alzheimer-like pathology - Guillot-Sestier, Marie-Victoire (Neuron, 2015)
The impact of inflammation suppressor pathways on Alzheimer’s disease (AD) evolution remains poorly understood. Human evidence suggests involvement of the cardinal anti-inflammatory cytokine, interleukin-10 (Il10). We crossed the APP/PS1 mouse model of cerebral amyloidosis with a mouse deficient in Il10 (APP/PS1(+)Il10(−/−)). Quantitative in silico 3D modeling revealed activated Aβ phagocytic microglia in APP/PS1(+)Il10(−/−) mice that restricted cerebral amyloidosis. Genome-wide RNA sequencing of APP/PS1(+)Il10(−/−) brains showed selective modulation of innate immune genes that drive neuroinflammation. Il10 deficiency preserved synaptic integrity and mitigated cognitive disturbance in APP/PS1 mice. In vitro knock-down of microglial Il10-Stat3 signaling endorsed Aβ phagocytosis, while exogenous IL-10 had the converse effect. Il10 deficiency also partially overcame inhibition of microglial Aβ uptake by human Apolipoprotein E. Finally, the IL-10 signaling pathway was abnormally elevated in AD patient brains. Our results suggest that ‘re-balancing’ innate immunity by blocking the IL-10 anti-inflammatory response may be therapeutically relevant for AD.